Life Cycle Assessment on the Direct Recycling Aluminium Alloy AA6061 Chips and Metal Matrix Composite (MMC-AlR) - Yusuf, N.K.; Lajis, M.A.; Ahmad, A. (International Journal of Integrated Engineering, 2021)
Metallic material processing plays a significant role in terms of global environmental impact which contributes to the climate change phenomena that is a serious international environmental concern and the subject of much research and debate. Thus, energy- and resource-efficient strategies in the metal shaping technology domain need to be identified urgently. A frequent theme in the debates that surround waste and resources management is the extent to which the recycling of metallic materials offers genuine benefits to the environment. Solid state recycling techniques allow the manufacture of high density aluminium alloy parts directly from production scrap. In this paper the environmental impacts associated with ‘meltless’ scrap processing routes through hot press forging process with varying parameter has been studied. A comparative analysis has been performed with two different type of materials which is recycling aluminium alloy (AA6061) chips and metal matrix composite (AA6061 chips + 2% alumina) in order to quantify and compare the environmental benefits for both materials. The LCA data are collected using Simapro 8.0.4 software. The additional materials used in a product resulted higher environmental impact. Metal matrix composite had higher value of midpoint and endpoint impact categories compare to aluminium alloy chips.